What is the essence of an essence? : comparing Afro-relational and Western-individualist ontologies - Metz, Thaddeus (Array, 2019)
The dominant view amongst contemporary Western philosophers about the essence of a natural object is that it is constituted by its intrinsic properties. The ontological approach salient in the African philosophical tradition, in contrast, accounts for a thing’s essence by appeal to its relational properties. The Afro-relational ontology is under-developed, with the primary aim of this article being to help rectify that weakness. Specifically, this article’s aims are: to articulate an African approach to understanding the essence of a concrete, natural thing in terms of its relationships; to illustrate the Afro-relational approach with the examples of the self and of water; to contrast the Afro-relational characterization of the essence of the self and of water with a typically Western construal in terms of their intrinsic properties; and finally to provide an initial defence of the Afro-relational approach, both by responding to some objections facing it and by providing some new, positive reasons to take it seriously.